A Question of Human Rights or Human Left? – The 'People's War against COVID-19' under the 'Gridded Management' System in China. Issue 136 (4th July 2022) - Jiang, Jue
ABSTRACT: The 'gridded management' system is officially highlighted as playing a key role in China's combat against COVID-19. Relying largely on the Maoist ideology of the 'Mass Line, ' this system appears to effectively mobilize the people at the most grassroots level in the 'war against COVID-19.' This article, drawing upon a critical examination of this 'People's War' from a Foucauldian governmentality perspective, discusses the violation of human rights and dignity and argues that the violations are inherent in the binary and utilitarian ideology of the 'Mass Line' deployed by the mobilizational party. As this methodology is embedded in China's social management agenda raised by Xi Jinping in 2017, this article sheds crucial light on the 'Chinese vision of human rights' and China's governance model today.